Psychoeducation to Reduces Anxiety in Primigravida Mothers at the Rumah Tumbuh Harapan Foundation - Hilda Soedjito; Evany Victoriana; F. Anindya Dwi Puspa Ningrum (Journal of Innovation and Community Engagement, 2023)
Pregnancy can cause discomfort for the changes experienced by a mother, namely physical changes, changes in social functioning, and psychological changes. The first pregnancy for a mother is a new journey where one of the influential psychological aspects is anxiety. Anxiety during pregnancy is also experienced by primigravida pregnant women who become pregnant outside of marriage. The anxiety that is felt is due to the mother's concern for the child's health, the mother's ability to take care of the child, how to carry out the role as a mother, how the environment views her, economic conditions, and family conditions. This has an impact not only on the psychological condition of pregnant women so that they experience high and moderate levels of anxiety, but also on the condition of the exposed fetus. The Foundation's management said that this anxious mother gave rise to behavioral reactions such as irritability and crying easily. The method used to overcome this problem is psychoeducation to reduce anxiety. The results and conclusions of the psychoeducation carried out are that psychoeducation can increase knowledge and understanding of anxiety and ways to overcome it so that it can effectively reduce anxiety.